THE IMPLICATIONS OF LIFELONG EDUCATION ON IMPROVEMENT OF MORALS AND SELF POTENTIAL: In Belief of Islam and Guthrie's Thought - Giyanti, Ummu Ahya (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2023)
This study aims to analyze implications of lifelong education on morals and human potential in Islamic views and Guthrie thought. The method carried out in this study is a literature review, which is a research approach that reviews literature both with literature studies and direct observations in the field. The results of this study show that lifelong education be a concern for many parties. When related in a wide area, Islamic conception and western scientist or philosopher give attention about the urgency of lifelong education although with different approaches. The implications that arise from lifelong education are the development and improvement of morals and the potential of human personality in accordance with its nature and essence, fostering awareness that the process of growth and development of human personality is alive and dynamic, and can increase human life expectancy. Keywords: Lifelong Education, Morals, Self-Potential